Psychological Well-Being Pada Mahasiswa Rantau: Adakah Pengaruh Dari Dukungan Sosial dan Penyesuaian Diri? - Eviliani, Afrisa; Nurhayaty, Any; Syah, Tansri Adzlan (Jurnal Ilmiah Psyche, 2024)
Psychological well-being is a condition where individuals feel their life is meaningful when they are able to demonstrate and gain personal self-acceptance, control over the environment, have convincing interpersonal relationships, personal growth and autonomy, several factors that can influence psychological well-being. Welfare can lead to social service support provided by someone with good adjustment. The purpose of this research is to determine the effect of social support and adjustment on the psychological well-being of overseas students. The instruments used in this research were the Ryff's Scale of Psychological Well-Being (RSPWB) developed by Ryff, the Social Provision Scale by Cutrona, C.E and Russel as a social support scale, and a self-adjustment scale compiled based on six aspects based on opinions from Schneiders as many as 30 items. Data analysis techniques are used to test the hypothesis and correlation with the help of SPSS version 25 data processing. The results of the research suddenly show a correlation that leads to social support and self-adjustment which is associated with the psychological well-being of overseas students,recorded with a correlation coefficient of 0.692 and a significance score of 0.000 (p > 0.05). Thus the hypothesis proposed in this research is accepted.